Controllable liquid metal boundaries to improve microwave heating efficiency and uniformity in food processing - Junwei Wang; Bin Yao; Rui Gong; Qinhong Zheng; Yingkai Liu; Runeng Zhong; Tai Xiang (Current Research in Food Science)
This study proposes an innovative microwave reaction cavity (MRC) design incorporating height-controllable liquid metal boundaries (HCLMBs) to address the persistent challenges of low heating efficiency and poor heating uniformity associated with conventional microwave heating in food processing. Firstly, the HCLMBs are realized by strategically positioning glass tube arrays along the wall-side of the MRC and injecting specified liquid metal volume into the glass tubes. Then, based on the proposed HCLMBs, three boundary modulation heating methods are systematically developed to achieve different microwave heating performances. Furthermore, the influence of the adjustment sequence of the liquid metal columns on the heating performance is also investigated. Numerical simulations demonstrated significant improvements over conventional MRC (CMRC) systems, with the MRC incorporating HCLMB achieving maximum enhancements of 107.54 % in heating efficiency and 201.85 % in heating uniformity. In addition, a corresponding experimental microwave heating system is built to validate the simulation results. Finally, the applicability of the HCLMB and boundary modulation heating methods to foods of different shapes and materials is discussed, demonstrating its potential for food processing applications.